Maternal Tobacco and Alcohol Use in Relation to Child Malnutrition in Gauteng, South Africa: A Retrospective Analysis - Perpetua Modjadji; Mpinane Pitso (MDPI AG, 2021)
Tobacco and alcohol use among mothers is associated with numerous adverse consequences for affected offspring, including poor growth and development. This study determined the association between maternal tobacco and alcohol use, and malnutrition, among infants aged ≤ 12 months (n = 300), in selected health facilities situated in Gauteng, South Africa. Data on alcohol and tobacco use were collected using a validated questionnaire, in addition to mothers' socio-demographic characteristics and obstetric history. Stunting (low height/length-for-age), underweight (low weight-for-age) and thinness (low body mass index-for-age) were calculated using z-scores based on the World Health Organization child growth standards. The association of tobacco and alcohol use with stunting, underweight and thinness was analysed using logistic regression analysis. The results showed a mean age of 29 years (24.0; 35.0) for mothers and 7.6 ± 3 months for infants, and over half of the mothers were unemployed (63%). Approximately 18.7% of mothers had used tobacco and 3% had used alcohol during pregnancy. The prevalence of current tobacco and alcohol use among mothers were estimated at 14.3% and 49.7%, respectively, and almost three-quarters (67.3%) of them were still breastfeeding during the study period. Stunting (55%) was the most prevalent malnutrition indicator among infants, while underweight was 41.7%, and thinness was 22%. Current tobacco use was associated with increased odds of being thin [OR = 2.40, 95% CI: 1.09-5.45), and after adjusting for confounders, current alcohol use was associated with the likelihood of being underweight [AOR = 1.96, 95% CI: 1.06-3.63] among infants. Future prospective cohort studies that examine growth patterns among infants who are exposed to maternal tobacco and alcohol use from the intrauterine life to infancy are necessary to inform, partly, the public health programmes, to reduce malnutrition among children.